2019
DOI: 10.3168/jds.2018-15468
|View full text |Cite
|
Sign up to set email alerts
|

Increase in aflatoxins due to Aspergillus section Flavi multiplication during the aerobic deterioration of corn silage treated with different bacteria inocula

Abstract: The growth of Aspergillus flavus and the production of aflatoxins (AF) during the aerobic deterioration of corn silage represent a problem for animal and human health. This experiment was conducted to evaluate whether the presence of A. flavus and AF production originate from the field or additional AF are produced during the fermentation phase or during aerobic deterioration of corn silage. The trial was carried out in northern Italy on corn at a dry matter (DM) level of 34%. The fresh herbage was either not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 57 publications
4
34
0
2
Order By: Relevance
“…Thus, in this study, the highest number of contaminated samples by A. fumigatus was found after 60 days of silage conservation, indicating that the fungus was able to survive 60 days under anaerobic conditions. Whereas, after longer conservation period (160 days of anaerobic condition), the number of samples containing A. fumigatus was low, as reported previously by Ferrero et al . The occurrence of A. fumigatus in corn silages at opening was previously described by Dolci et al .…”
Section: Discussionsupporting
confidence: 80%
“…Thus, in this study, the highest number of contaminated samples by A. fumigatus was found after 60 days of silage conservation, indicating that the fungus was able to survive 60 days under anaerobic conditions. Whereas, after longer conservation period (160 days of anaerobic condition), the number of samples containing A. fumigatus was low, as reported previously by Ferrero et al . The occurrence of A. fumigatus in corn silages at opening was previously described by Dolci et al .…”
Section: Discussionsupporting
confidence: 80%
“…Leuconostoc, and Pediococcus (P. pentosaceus) genera can inhibit or can even prevent completely the growths of various mycotoxigenic molds and their mycotoxin productions as well (Dalié et al, 2010;Cavallarin et al, 2011;Queiroz et al, 2012;Dogi et al, 2013;Ahlberg et al, 2015;Ma et al, 2017;Gallo et al, 2018;Zielińska and Fabiszewska, 2018;Ferrero et al, 2019). It is noteworthy that there is a wide spectrum of environmental factors which influence the antifungal activity of LAB, including the type of the matrix and culture medium, the availability of nutritional compounds, the incubation time and temperature (Dalié et al, 2010;Ahlberg et al, 2015;Leyva Salas et al, 2017).…”
Section: Microbial Biocontrol and Microbial Detoxification Products Fmentioning
confidence: 99%
“…The interaction of L. buchneri, L. reuteri, L. plantarum, and L. fermentum strains reduced the AFB 1 level, improved the stability and, furthermore, the microbiological and chemical purity of maize silage (Zielińska and Fabiszewska, 2018). In a most recent study by Ferrero et al (2019), the authors examined the effect of L. buchneri, Lactobacillus hilgardii, and their combination on A. flavus contaminants and their aflatoxin production in maize silage. The results showed that the inoculation of corn silage with L. buchneri and L. hilgardii increased the aerobic stability and delayed the beginning of aerobic microbial degradation of maize silage, and indirectly reduced the risk of A. flavus emergence and aflatoxin B 1 level after silage opening.…”
Section: Microbial Biocontrol and Microbial Detoxification Products Fmentioning
confidence: 99%
“…have been reported to inhibit growth of aflatoxin-producing Aspergillus spp. [15][16][17][18][19][20]. Yeast has also been used in some research to help animal performance and ruminal metabolism and to detoxify mycotoxins in feed [16,21].…”
Section: Introductionmentioning
confidence: 99%